2022
DOI: 10.3390/ijms23084404
|View full text |Cite
|
Sign up to set email alerts
|

Ostarine-Induced Myogenic Differentiation in C2C12, L6, and Rat Muscles

Abstract: Ostarine (also known as enobosarm or Gtx-024) belongs to the selective androgen receptor modulators (SARMs). It is a substance with an aryl-propionamide structure, classified as a non-steroidal compound that is not subjected to the typical steroid transformations of aromatization and reduction by α5 reductase. Despite ongoing research on ostarine, knowledge about it is still limited. Earlier studies indicated that ostarine may affect the metabolism of muscle tissue, but this mechanism has not been yet describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Growing evidence demonstrates that the lipid metabolism of peripheral tissues is modulated by peptide hormones [2]. Leciejewska et al focused on the role of the spexin hormone in controlling the development and metabolism of muscle cells [3]. The authors demonstrated that spexin promotes the replication of the skeletal muscle cell line C2C12 and the differentiation of these cells into muscles.…”
mentioning
confidence: 99%
“…Growing evidence demonstrates that the lipid metabolism of peripheral tissues is modulated by peptide hormones [2]. Leciejewska et al focused on the role of the spexin hormone in controlling the development and metabolism of muscle cells [3]. The authors demonstrated that spexin promotes the replication of the skeletal muscle cell line C2C12 and the differentiation of these cells into muscles.…”
mentioning
confidence: 99%